DIGITALIZATION OF ETHNOMATHEMATICS THROUGH THE STEM APPROACH: LANGGAR ETNOMATEMATIKA DIGITAL (LEDI) CARD BASED ON AUGMENTED REALISTICS - Wulan Sutriyani; Riska Anintyawati; Siti Fatimah; Dwiana Asih Wiranti; Aan Widiyono; Abdullah Efendi; Ahmat Wakit (Universitas Labuhanbatu, 2026)
Purpose - This study aims to describe the development stages and test the feasibility, effectiveness, and practicality of the LEDI Card (Langgar-Ethnomatematika Digital) media, based on Augmented Reality (AR) and a STEM approach, as a contextual and meaningful innovation in geometry learning.Methodology - This study employed a Research and Development approach using the ADDIE model. The trial involved two subject matter experts, two media experts, and 31 fifth-grade elementary school students as the primary subjects. Data analysis was conducted comprehensively using qualitative and quantitative approaches.Findings - The results of the study show: (1) AR-based LEDI Card media was successfully developed through five systematic stages of the ADDIE model by integrating STEM elements and ethnomathematics of Jepara's 'Langgar' architecture. (2) LEDI Card media was declared very valid based on the results of the material expert validity test (80.3%) and the results of the media expert validity test (91%). The results of the paired-sample T test showed a significant difference between pretest and posttest learning outcomes (Sig. 0.000 < 0.05), while the N-Gain test result of 0.60 was in the moderate category, indicating a fairly effective interpretation. (3) The media was considered very practical based on teacher responses (81%) and student responses (85.4%).Contribution - Particularly by demonstrating that integrating ethnomathematics, STEM, and AR technology can reduce cognitive load, reduce math anxiety, and present mathematics as a contextual, inclusive, and enjoyable discipline while honoring local cultural roots.